Effects of 6% Tetrastarch and Lactated Ringer's Solution on Extravascular Lung Water and Markers of Acute Renal Injury in Hemorrhaged, Isoflurane-Anesthetized Healthy Dogs - Diniz, M. S. [UNESP]; Teixeira-Neto, F. J. [UNESP]; Celeita-Rodriguez, N. [UNESP]; Girotto, C. H. [UNESP]; Fonseca, M. W. [UNESP]; Oliveira-Garcia, A. C. [UNESP]; Lopez-Castaneda, B. [UNESP] (Wiley-Blackwell, 2018)
BackgroundTetrastarch can cause acute kidney injury (AKI) in humans with sepsis, but less likely to result in tissue edema than lactated Ringer's solution (LRS). ObjectivesCompare effects of volume replacement (VR) with LRS and 6% tetrastarch solution (TS) on extravascular lung water (EVLW) and markers of AKI in hemorrhaged dogs. AnimalsSix healthy English Pointer dogs (19.7-35.3 kg). MethodsProspective crossover study. Animals underwent anesthesia without hemorrhage (Control). Two weeks later, dogs hemorrhaged under anesthesia on 2 occasions (8-week washout intervals) and randomly received VR with LRS or TS at 3 : 1 or 1 : 1 of shed blood, respectively. Anesthesia was maintained until 4 hour after VR for EVLW measurements derived from transpulmonary thermodilution cardiac output. Neutrophil gelatinase-associated lipocalin (NGAL) and creatinine concentrations in plasma and urine were measured until 72 hour after VR. ResultsThe EVLW index (mL/kg) was lower at 1 hour after TS (10.0 1.9) in comparison with controls (11.9 +/- 3.4, P = 0.04), and at 4 hour after TS (9.7 +/- 1.9) in comparison with LRS (11.8 +/- 2.7, P = 0.03). Arterial oxygen partial pressure-to-inspired oxygen fraction ratio did not differ among treatments from 0.5 to 4 hour after VR. Urine NGAL/creatinine ratio did not differ among treatments and remained below threshold for AKI (120,000 pg/mg). Conclusions and Clinical ImportanceAlthough TS causes less EVLW accumulation than LRS, neither fluid produced evidence of lung edema (impaired oxygenation). Both fluids appear not to cause AKI when used for VR after hemorrhage in healthy nonseptic dogs.
Keywords: Colloids; Crystalloids; Hydroxyethyl starch; Neutrophil gelatinase-associated lipocalin